Sistemas de auto-alimentação para avaliar o consumo de nutrientes e ritmos diários da atividade alimentar em pirarucu (Arapaima gigas) - Mattos, Bruno Olivetti de (2018)
Daily feeding rhythms and the ability of pirarucu (Arapaima gigas) to compose a balanced diet through macronutrient self-selection were evaluated. Twelve fish (1573.3 ± 74.4 g) were distributed in six tanks of 250 l, two fish per tank. First, three experimental diets were prepared using an incomplete mixture of macronutrients (75%protein/25%carbohydrate-PC, 75%protein/25%fat-PF and 10% protein/45%fat/45%carbohydrate-PFC). These diets were provided to fish through a self-feeding system connected to a computer to record feeding activity. After this procedure, fish were challenged with a 50% protein dilution (diets: PC50 and PF50). The results showed that pirarucu exhibited a strict diurnal feeding pattern with 95.4% of daily feeding activity observed in the daytime. Fish selected 56.3% P, 24.2% C, 19.5% F, and consumed 150-151 kJ/kg BW/day of energy. After protein dilution, fish sustained energy intake by increasing the consumption of PC50 and PF50 to maintain the target protein intake of the previous stage. When fish were protein-restricted, they failed to sustain previous energy intake. These findings can be used to design feeding regimes and for formulating aquafeed for pirarucu.